Domestic fridge-freezer load aggregation to support ancillary services. (March 2016) - Martin Almenta, M.; Morrow, D.J.; Best, R.J.; Fox, B.; Foley, A.M.
Abstract: Grid operators and electricity retailers in Ireland manage peak demand, power system balancing and grid congestion by offering relevant incentives to consumers to reduce or shift their load. The need for active consumers in the home using smart appliances has never been greater, due to increased variable renewable generation and grid constraints. In this paper an aggregated model of a single compressor fridge-freezer population is developed. A price control strategy is examined to quantify and value demand response savings during a representative winter and summer week for Ireland in 2020. The results show an average reduction in fridge-freezer operating cost of 8.2% during winter and significantly lower during summer in Ireland. A peak reduction of at least 68% of the average winter refrigeration load is achieved consistently during the week analysed using a staggering control mode. An analysis of the current ancillary service payments confirms that these are insufficient to ensure widespread uptake by the small consumer, and new mechanisms need to be developed to make becoming an active consumer attractive. Demand response is proposed as a new ancillary service called ramping capability, as the need for this service will increase with more renewable energy penetration on the power system. Highlights: Modelling of an aggregated fridge-freezer load using price signal control strategy. Fridge-freezer can provide regulating reserve, specifically ramping capability. Variable tariffs lead to overall reduction on fridge-freezer operation costs. Appropriately rewarding ancillary services need to be developed.